Prospects for use of finely disperse quartz sands in production of foam-glass crystalline materials; Glass and Ceramics; Vol. 65, N 9-10 - Kazmina O. V. Olga Viktorovna (2008, 2008)
Use of finely disperse Tuganskoe quartz sands (Tomsk Oblast) in production of foam-glass crystalline materials by low-temperature synthesis of glass granulate instead of cullet was investigated. The important possibility of manufacturing foam-glass crystalline materials with basic process properties as good as traditional foam glass made from cullet was established